APPLICATION PROGRAM FOR AUDIO AND VIDEO PLAYER WITH DELPHI 6 USING WINDOWS MEDIA PLAYER ACTIVEX CONTROLS - Tony Sugiarto (Jurnal Manajemen Informatika, 2010)
Along with the development of computer technology is so rapid, computers today arenot only used as a tool for the job but it can also be used as a medium ofentertainment, like to listen to music or watching videos, so you no longer need suchmedia.In the play the audio and video via computer media, there are two things to note areused to build computers and software programs have facilities incorporating elementsof audio and video in one software. Software that can be used vary from simple to onthat have a high level of complexity. Each level in the variation affects the level ofthe software is user satisfaction. Many of the actual product that can be selected toplay audio and video, but distinguished between programming languages withSotware authoring.